Repatriation is associated with isthmus cingulate cortex reduction in community-dwelling elderly. (18th August 2018) - Calati, Raffaella; Maller, Jerome J; Meslin, Chantal; Lopez-Castroman, Jorge; Ritchie, Karen; Courtet, Philippe; Artero, Sylvaine
Abstract: Objectives: The impact of stressful life events (SLEs) on brain anatomy is poorly understood, particularly its long-term neural consequences. We tested the hypothesis that a serious SLE (repatriation of French citizens living in Algeria in 1962) is associated with changes in brain regions previously implicated in psychopathology (hippocampus, amygdala, corpus callosum, prefrontal cortex, anterior, posterior and isthmus cingulate cortex (ICC)) in a large elderly population. Methods: Structural magnetic resonance imaging was used to acquire anatomical scans from 82 subjects repatriated from Algeria and 339 subjects without this experience or any other trauma. We derived quantitative regional estimates of subcortical volume using FreeSurfer Software. The General Linear Model was used to test the association between repatriation and changes in brain volume adjusted for confounders (gender, age, education, total brain volume, traumatic brain injury, Mini Mental State Examination score at baseline, current and lifetime major depression and recent SLEs). Results: Repatriation to France was associated with reduced volume in a number of areas; however, only left and right ICC survived to false discovery rate correction. Conclusions: In the elderly a previous (approximately 40 years before) serious SLE could be associated with long-term volume reduction in the ICC, independently of psychopathology.